2022
DOI: 10.1093/sleep/zsac100
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances among women in a Subarctic region: a nationwide study

Abstract: Study objectives To date, few studies have assessed sleep problems among women residing in Subarctic regions. Therefore, the aim of this large-scale population-based study was to assess the prevalence of severe sleep problems and associated factors among Icelandic women, living at 63-66°N. Methods Participants were 29,681 women (18-69 years old) who took part in the Icelandic Stress-And-Gene-Analysis study in 2018–2019. Backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The Arctic light environment is challenging to the circadian system, health and wellbeing [11][12][13][14][15][16]. Previous studies also suggested that disruption of the circadian system has an adverse impact on metabolic health [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The Arctic light environment is challenging to the circadian system, health and wellbeing [11][12][13][14][15][16]. Previous studies also suggested that disruption of the circadian system has an adverse impact on metabolic health [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%